Respostas

2014-06-03T15:47:03-03:00
2x+y=5                                                        2x+y=5                                     
x+y=3                                                            x+y=3 caso eu multiplicar a 2° por (-1)
x=3-y                                                            2x+y=5  
                                                                       -x-y=-3 LOGO (cortando o Y)
2(3-y)+y=5                                                                  2x-x=5-3
 6-2y+y=5-6                                                                   x=2
-y=-1 .(-1)                            ou                           x+y=3
y=1                                                                    2+y=3
                                                                          y=3-2
x+y=3                                                                 y=1
x+1=3
x=3-1
x=2